Post-traumatic stress disorder and neurofeedback: evaluating the effectiveness of therapy among Ukrainian military personnel - Voznitsyna Ксенія; Oliinyk Олена (Psychosomatic Medicine and General Practice, 2024)
Relevance Post-traumatic stress disorder (PTSD) is a serious mental illness that often occurs in people who have experienced traumatic events, especially in the military who have participated in combat. PTSD is accompanied by symptoms such as anxiety, depression, intrusive memories, and emotional instability, and can significantly reduce the quality of life of patients. Traditional treatments, such as medication and psychotherapy, are often not effective enough or cause side effects, prompting the search for alternative approaches. One of the most promising methods is neurofeedback, an innovative approach aimed at improving self-regulation of brain activity through monitoring and training of brain waves. Neurofeedback allows patients with PTSD to learn to control their psycho-emotional states, reduce stress and improve concentration. This method is especially important for the military, who often experience PTSD after combat. In combination with medication therapy, neurofeedback enhances the effectiveness of treatment, promoting long-term positive changes and improving the quality of life of patients, making it an important tool in rehabilitation. Aims. To evaluate the effectiveness of neurofeedback in reducing PTSD and anxiety symptoms in Ukrainian military personnel, as well as to study the impact of this therapy on the psychoemotional state and quality of life of patients. Materials and methods. The study involved 55 servicemen aged 19-65 years who suffered from PTSD. The PCL-M questionnaire and the SUDS scale for stress level were used to assess the condition. All patients underwent neurofeedback therapy with brain activity monitoring using EEG from the Callibri technology unit. The data were analysed to identify the relationship between PTSD symptoms and changes in brain activity. Results. Neurofeedback therapy showed an average reduction in PTSD symptoms by 7.67 points on the PCL-M scale. 65% of patients had an improvement of more than 5 points, and 15% had minor changes. The level of stress decreased by 2.14 points on the SUDS scale, with 70% of patients showing a reduction of 2 points or more. EEG showed slight changes in brain activity (+0.25 points). 5% of patients had a slight worsening of symptoms, which emphasises the importance of an individual approach to therapy. Conclusion. Our study confirmed the promise of neurofeedback in the treatment of military personnel suffering from PTSD, demonstrating a significant improvement in the psychoemotional state of patients and a reduction in symptoms and stress levels. However, some individual variations in response to therapy have been reported, including a slight worsening of the condition in some cases. The uniqueness of our study lies in the focus on military personnel from Ukraine, which adds context to the evaluation of the effectiveness of neurofeedback in an active conflict setting. This underscores the need for further research to examine the long-term effects of the therapy and its adaptation to chronic stress, using a larger sample of patients and longer periods of therapy.